MEASUREMENT OF EFFICIENCY AND EFFECTIVENESS OF THAILAND LOW-COST AIRLINE MANAGEMENT USING MARKETING-MIX (7PS) THEORY - Akkapin, Supaphorn; Kaewniam, Chamnong; Detdamrongpreecha, Butsarin; Madpongtua, Waris; Thanarakwattanakul, Thaninthorn; Seedanoy, Darin (RMUTK Journal of Liberal Arts, 2022)
This research aims to 1) observe the demographic details of the clients of low-cost airlines operating in Thailand, and 2) measure efficiency and effectiveness of Thailand’s low-cost airlines using the marketing mix (7PS) theory. The qualitative research employed the questionnaire to collate the data from the sample which are 100 clients of Thailand’s low-cost airlines. The accidental sampling was conducted at Suvarnabhumi International Airport, Samut Prakan and Don Mueang International Airport, Bangkok. The data were analyzed by descriptive statistics i.e., frequency, percentage (%), mean (), and standard deviation (S.D.) applied with the marketing-mix theory (7Ps). The results revealed that the majority of Thailand airline clients were female (56%), aged 26-35 years (34%), single status (47%), holding a bachelor’s degree (61%), were private-sector employees (47%), and average monthly income 10,001-20,000 Baht (28%). According to the measurement of efficiency and effectiveness of Thailand’s low-cost airlines using marketing mix (7PS) theory, the results revealed that most of the clients had an opinion on the efficiency and effectiveness of the overall low-cost airline business management at the highest level ( =3.65, SD=1.11), by having an opinion on the airline personnel at the highest level ( =4.13, SD=0.69). However, the opinion of clients on the marketing promotion was at a moderate level ( =3.74 SD=0.8), which was the lowest opinion of the efficiency and effectiveness of the low-cost management operated in Thailand.